Valorization of local legumes and nuts as key components of the mediterranean diet - Hernández-López, Israel (2022)
Legumes and nuts are components of high importance in the diet of many countries, mainly those in the Mediterranean region. They are also very versatile and culturally diverse foods found all over the world, acting as a basic protein source in certain countries. Their genetic diversity is needed to sustain the food supply and security for humans and livestock, especially because of the current loss of habitats, species, and genetic diversity worldwide, but also because of the ever present need to feed the increasing human population. Even though both legumes and nuts are considered as high-protein food and environmentally friendly crops, developed countries have lower consumption rates when compared to Asia or Africa. With a view to increasing the consumption of legumes and nuts, the objective of this review is to present the advantages on the use of autochthonous varieties from different countries around the world, thus providing a boost to the local market in the area. The consumption of these varieties could be helped by their use in ready-to-eat foods (RTE), which are now on the rise thanks to today’s fast-paced lifestyles and the search for more nutritious and sustainable foods. The versatility of legumes and nuts covers a wide range of possibilities through their use in plant-based dairy analogues, providing alternative-protein and maximal amounts of nutrients and bioactive compounds, potential plant-based flours for bakery and pasta, and added-value traditional RTE meals. For this reason, information about legume and nut nutrition could possibly increase its acceptance with consumers.